Diversification of urban water supply: An assessment of social costs and water production costs - Francisco W. Ribeiro; Samiria M. O. da Silva; Francisco de A. de Souza Filho; Taís M. N. Carvalho; Tereza M. X. de M. Lopes (Water Policy, 2022)
The incorporation of new water sources into a supply system requires an assessment of their economic feasibility, which, in turn, demands knowledge of their associated costs. This study calculates water production cost and evaluates social cost by applying the residual value method and calculating the shadow price for several water sources. The results indicate that desalination and industrial reuse incur similar costs, with the former being more competitive in terms of investment (US dollar (USD) 0.28/m3) and the latter in operation and maintenance (USD 0.57/m3). Cisterns and greywater reuse incur higher investment costs (USD 2.20/m3 and USD 2.60/m3, respectively), while well water has the lowest total cost (USD 0.08/m3). Desalination showed the lowest degree of distortion between shadow price and water cost and between shadow price and the average tariff; meanwhile, there was moderate distortion for industrial reuse and groundwater sources. The conclusions suggest that desalination and industrial reuse offer good flow at feasible costs and are, therefore, strategically sound sources. However, for these sources and for wells, tariff policy does not reflect a significant part of the social cost they incur. HIGHLIGHTS Diversification of water supply is essential to increase water security of urban areas.; Industrial reuse has the highest shadow price and desalination, the highest water cost among alternative water sources.; Industrial reuse and wells have a higher distortion between shadow price and average water tariff than desalination.;